Strategies for Developing Fine Motor Skills in Children Aged 5-6 Years Through Weaving Cassava Leaf Stalks: A Case Study at Tamrinussibyan Islamic Kindergarten - Maknun, Lukluul; Zulfahmi, Muhammad Nofan (STAI Auliaurrasyidin Tembilahan, 2025)
Early childhood development is a critical period for the formation of basic skills and personality, particularly between the ages of 5-6 years. The use of cassava leaf stalks as a weaving medium is an innovative approach in early childhood education. This study aims to analyze the impact of cassava leaf stalk weaving activities on the fine motor development of children aged 5-6 years at Tamrinussibyan Islamic Kindergarten. This activity was chosen because it enhances hand-eye coordination and provides an enjoyable creative experience. The research employed a qualitative descriptive approach, with a population of 14 children aged 5-6 years. Data were collected through observation, interviews, and documentation. Data analysis involved reduction, presentation, and conclusion drawing. Triangulation was used to ensure data validity and accuracy. The results indicated that weaving activities using cassava leaf stalks significantly improved children's fine motor skills, enabling them to perform complex movements and express creativity. This study recommends integrating weaving activities into early childhood education curricula as an effective method for supporting fine motor development.